2021
DOI: 10.1002/ccr3.3983
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia secondary to iron deficiency anemia responding to iron therapy

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Thrombocytopenia resulting from ferrous medications is an exceedingly rare phenomenon, with less than 30 cases reported in the literature. Eisa et al 6 described a case of severe iron deficiency anemia that resulted in a transient drop in platelet counts after receiving intravenous ferrous carboxy maltose. A review by Babikir et al 7 found 20 patients who suffered from iron replacement-induced thrombocytopenia in 11 case reports and one case series.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia resulting from ferrous medications is an exceedingly rare phenomenon, with less than 30 cases reported in the literature. Eisa et al 6 described a case of severe iron deficiency anemia that resulted in a transient drop in platelet counts after receiving intravenous ferrous carboxy maltose. A review by Babikir et al 7 found 20 patients who suffered from iron replacement-induced thrombocytopenia in 11 case reports and one case series.…”
Section: Discussionmentioning
confidence: 99%